Effect of decompression‐induced bubble formation on highly trained divers microvascular function. Issue 6 (7th November 2013) - Lambrechts, Kate; Pontier, Jean‐Michel; Mazur, Aleksandra; Buzzacott, Peter; Morin, Jean; Wang, Qiong; Theron, Michael; Guerrero, Francois
Abstract: We previously showed microvascular alteration of both endothelium‐dependent and ‐independent reactivity after a single SCUBA dive. We aimed to study mechanisms involved in this postdive vascular dysfunction. Ten divers each completed three protocols: (1) a SCUBA dive at 400 kPa for 30 min; (2) a 41‐min duration of seawater surface head immersed finning exercise to determine the effect of immersion and moderate physical activity; and (3) a simulated 41‐min dive breathing 100% oxygen (hyperbaric oxygen [HBO]) at 170 kPa in order to analyze the effect of diving‐induced hyperoxia. Bubble grades were monitored with Doppler. Cutaneous microvascular function was assessed by laser Doppler. Endothelium‐dependent (acetylcholine, ACh) and ‐independent (sodium nitroprusside, SNP) reactivity was tested by iontophoresis. Endothelial cell activation was quantified by plasma Von Willebrand factor and nitric oxide (NO). Inactivation of NO by oxidative stress was assessed by plasma nitrotyrosine. Platelet factor 4 (PF4) was assessed in order to determine platelet aggregation. Blood was also analyzed for measurement of platelet count. Cutaneous vascular conductance (CVC) response to ACh delivery was not significantly decreased by the SCUBA protocol (23 ± 9% before vs. 17 ± 7% after; P  =   0.122), whereas CVC response to SNP stimulation decreased significantly (23 ± 6% before vs. 10 ± 1% after; P  =   0.039). The HBO and immersion protocols did not affect either endothelial‐dependent or ‐independent function. The immersion protocol induced a significant increase in NO (0.07 ± 0.01 vs. 0.12 ± 0.02  μ g/mL; P  =   0.035). This study highlighted change in microvascular endothelial‐independent but not ‐dependent function in highly trained divers after a single air dive. The results suggest that the effects of decompression on microvascular function may be modified by diving acclimatization. Abstract : e00142 This study points out the effect of diving on microcirculatory endothelium‐dependent and ‐independent function using laser Doppler flowmetry and plasmatic markers, which was not reported before to the best of our knowledge. These data may be helpful in the comprehension and in the prevention of the mechanism underlying decompression sickness.